Addition of Fermented Cassava Leaf Flour in Rations to Percentages of Native Chicken Carcass and Non-Carcass 10 Weeks Olds - I Gede Herys Setyawan; Ni Ketut Sri Rukmini; Ni Made Yudiastari (SEAS (Sustainable Environment Agricultural Science), 2023)
AbstractSuper free-range chicken, which is currently a very lucrative new business opportunity because the demand for free-range chicken meat has increased significantly due to high consumer demand. The type of agricultural waste that can be used as ration material is cassava leaves. The purpose of this study was to determine the effect of using fermented cassava leaf flour in the ration on the percentage of carcass and non-carcass chicken super aged 10 weeks, to find out what percentage level of use of fermented cassava leaf flour in the ration is able to provide the best results on the percentage of carcass and non 10 weeks old free-range chicken carcass. The research design used was a completely randomized design (CRD) which consisted of 5 treatments namely: L0 (without the addition of cassava leaf flour), L1 (ration containing 2.5% fermented cassava leaf flour), L2 (ration containing 5% starch) fermented cassava leaf), L3 (ration containing 7.5% fermented cassava leaf flour), L4 (ration containing 10% fermented cassava leaf flour). Each treatment was repeated 3 times. The use of cassava leaf meal in the ration had no significant effect (P>0.05) on carcass weight, non-carcass weight, carcass percentage and non-carcass percentage. The use of cassava leaf flour in the ration tends to be higher at the level of use of flour containing 5% fermented cassava leaf flour, but does not have a significant effect.